2014
DOI: 10.1002/hbm.22527
|View full text |Cite
|
Sign up to set email alerts
|

The influence of group membership and individual differences in psychopathy and perspective taking on neural responses when punishing and rewarding others

Abstract: Understanding how neural processes involved in punishing and rewarding others are altered by group membership and personality traits is critical in order to gain a better understanding of how socially important phenomena such as racial and group biases develop. Participants in an fMRI study (n = 48) gave rewards (money) or punishments (electroshocks) to in-group or out-group members. The results show that when participants rewarded others, greater activation was found in regions typically associated with recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 69 publications
6
39
0
1
Order By: Relevance
“…Prior work has consistently found that decisions to donate to others, including charities, strangers, and family members, recruits the ventral striatum (Harbaugh et al, 2007;Izuma et al, 2010;Moll et al, 2006;Telzer et al, 2010;Molenberghs et al, 2014). We build upon this work and show that striatal response when donating to unfamiliar others is modulated by group membership.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Prior work has consistently found that decisions to donate to others, including charities, strangers, and family members, recruits the ventral striatum (Harbaugh et al, 2007;Izuma et al, 2010;Moll et al, 2006;Telzer et al, 2010;Molenberghs et al, 2014). We build upon this work and show that striatal response when donating to unfamiliar others is modulated by group membership.…”
Section: Discussionmentioning
confidence: 68%
“…Given that individuals feel good when their own-group is doing well and that it is rewarding to belong to a social group (Tajfel, 1974), we hypothesized that prosocial decisions to help in-group members relative to out-group members would be associated with heightened rewardrelated activation. Indeed, prior work has shown that rewarding in-group members leads to increased activation in the ventral striatum and mOFC compared to rewarding out-group members (Molenberghs et al, 2014).…”
mentioning
confidence: 98%
“…The insula has long been implicated in empathy, the capability to understand and resonate with the affective experience of another, and is crucial in the inhibition of antisocial, aggressive behavior. Abnormal activation in the insula during empathy-related tasks has been linked to higher levels of psychopathy in several adult studies (Decety et al, 2013; Decety et al, 2014; Molenberghs et al, 2014). For developmental populations, prior studies on children with conduct problems have also demonstrated abnormal neural responses to others in pain in the insula (Sterzer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These studies included the observation of social targets experiencing a variety of reward types, including pleasant touch, tastes, and smells, monetary payoffs, positive social feedback (e.g., praise), and positive emotional events (e.g., getting engaged). Social distance between the participant and target varied across studies, ranging from strangers (Morelli et al, 2014) to friends and ingroup members (e.g., (Braams et al, 2013; Molenberghs et al, 2014; Varnum, Shi, Chen, Qiu, & Han, 2014) to family (Telzer, Fuligni, Lieberman, & Galván, 2013; Telzer, Masten, Berkman, Lieberman, & Fuligni, 2010). …”
Section: Methodsmentioning
confidence: 99%